Muscle specific kinase protects dystrophic mdx mouse muscles from eccentric contraction‐induced loss of force‐producing capacity. (18th August 2019) - Trajanovska, S.; Ban, J.; Huang, J.; Gregorevic, P.; Morsch, M.; Allen, D. G.; Phillips, W. D.
Abstract : Key points: Adeno‐associated viral vector was used to elevate the expression of muscle specific kinase (MuSK) and rapsyn (a cytoplasmic MuSK effector protein) in the tibialis anterior muscle of wild‐type and dystrophic ( mdx ) mice. In mdx mice, enhanced expression of either MuSK or rapsyn ameliorated the acute loss of muscle force associated with strain injury. Increases in sarcolemmal immunolabelling for utrophin and β‐dystroglycan suggest a mechanism for the protective effect of MuSK in mdx muscles. MuSK also caused subtle changes to the structure and function of the neuromuscular junction, suggesting novel roles for MuSK in muscle physiology and pathophysiology. Abstract: Muscle specific kinase (MuSK) has a well‐defined role in stabilizing the developing mammalian neuromuscular junction, but MuSK might also be protective in some neuromuscular diseases. In the dystrophin‐deficient mdx mouse model of Duchenne muscular dystrophy, limb muscles are especially fragile. We injected the tibialis anterior muscle of 8‐week‐old mdx and wild‐type (C57BL10) mice with adeno‐associated viral vectors encoding either MuSK or rapsyn (a cytoplasmic MuSK effector protein) fused to green fluorescent protein (MuSK‐GFP and rapsyn‐GFP, respectively). Contralateral muscles injected with empty vector served as controls. One month later mice were anaesthetized with isoflurane and isometric force‐producing capacity was recorded from the distal tendon. MuSK‐GFP caused an unexpected decay in nerve‐evoked tetanic force, both in wild‐type and mdx muscles, without affecting contraction elicited by direct electrical stimulation of the muscle. Muscle fragility was probed by challenging muscles with a strain injury protocol consisting of a series of four strain‐producing eccentric contractions in vivo . When applied to muscles of mdx mice, eccentric contraction produced an acute 27% reduction in directly evoked muscle force output, affirming the susceptibility of mdx muscles to strain injury. mdx muscles overexpressing MuSK‐GFP or rapsyn‐GFP exhibited significantly milder force deficits after the eccentric contraction challenge (15% and 14%, respectively). The protective effect of MuSK‐GFP in muscles of mdx mice was associated with increased immunolabelling for utrophin and β‐dystroglycan in the sarcolemma. Elevating the expression of MuSK or rapsyn revealed several distinct synaptic and extrasynaptic effects, suggesting novel roles for MuSK signalling in muscle physiology and pathophysiology. Key points: Adeno‐associated viral vector was used to elevate the expression of muscle specific kinase (MuSK) and rapsyn (a cytoplasmic MuSK effector protein) in the tibialis anterior muscle of wild‐type and dystrophic ( mdx ) mice. In mdx mice, enhanced expression of either MuSK or rapsyn ameliorated the acute loss of muscle force associated with strain injury. Increases in sarcolemmal immunolabelling for utrophin and β‐dystroglycan suggest a mechanism for the protective effect of MuSK in mdx muscles. MuSK also caused subtle changes to the structure and function of the neuromuscular junction, suggesting novel roles for MuSK in muscle physiology and pathophysiology.